Pathophysiological analysis of idiopathic sudden sensorineural hearing loss by magnetic resonance imaging: A mini scoping review - Sone, Michihiko; Kobayashi, Masumi; Yoshida, Tadao; Naganawa, Shinji (Frontiers in Neurology, 2023)
Objective: To summarize the pathophysiological analysis of idiopathic sudden sensorineural hearing loss (ISSNHL) by magnetic resonance imaging (MRI), focusing on the findings of high signal or endolymphatic hydrops (EH) in the inner ear. Methods: We summarize the published studies of our research group regarding the pathophysiological analysis of ISSNHL on MRI and review related clinical articles that have reported significantly high signal or the existence of EH in ears with ISSNHL. Results: Pre-contrast high signal on MRI may indicate minor hemorrhage or increased permeability of surrounding vessels to the perilymph, whereas post-contrast high signal indicates breakdown of the blood–labyrinth barrier, in which irreversible changes would lead to poor prognosis. In some cases of ISSNHL, primary EH could be pre-existing and may be a risk factor for the onset of ISSNHL. Conclusions: Analysis of ISSNHL by cutting-edge MRI evaluation could provide useful information for elucidating its pathophysiology and for predicting prognosis in this disease.